Effect of NaCl Activator Concentration on Iodine Adsorption of PET- based Activated Carbon - Agus, Fadilatur Rahmi; Yosef Barita Sar Manik (JST (Jurnal Sains dan Teknologi), 2024)
This study examines the use of NaCl as an activator in the production of activated carbon from Polyethylene terephthalate (PET) waste to overcome environmental problems due to the accumulation of plastic waste that is difficult to decompose. This study aims to examine the effect of NaCl concentration on the iodine adsorption capacity of activated carbon. This type of research is experimental research. The samples used were 15 samples of activated carbon. Data collection methods through laboratory experiments. Data analysis was performed by simple linear regression analysis. The results of the analysis showed that variations in NaCl concentration had a significant effect on iodine adsorption capacity, with an R² value of 0.868 indicating 86.8% of variations in adsorption capacity could be explained by NaCl concentration. A concentration of 1M was considered optimal in balancing effectiveness, production cost, and environmental impact, although higher concentrations resulted in better adsorption capacity. This study concludes that the utilization of PET waste for activated carbon production provides a sustainable solution to plastic pollution, reduces waste while producing high-value products for industrial applications, and contributes to the development of more environmentally friendly and economical activated carbon production methods.